2005
DOI: 10.1038/nrc1568
|View full text |Cite
|
Sign up to set email alerts
|

Testicular germ-cell tumours in a broader perspective

Abstract: The germ-cell tumours are a fascinating group of neoplasms because of their unusual biology and the spectacular therapeutic results that have been obtained in these tumours. Traditionally, this group of neoplasms is presented in an organ-oriented approach. However, recent clinical and experimental data convincingly demonstrate that these neoplasms are one disease with separate entities that can manifest themselves in different anatomical sites. We propose five entities, in which the developmental potential is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
931
5
8

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 829 publications
(1,006 citation statements)
references
References 151 publications
34
931
5
8
Order By: Relevance
“…Testicular germ cell tumors show a characteristic association with a preinvasive carcinoma in situ, the testicular intratubular neoplasia. 7,31,42 No such in situ lesion has been seen in the brain of patients with CNS-GCT. Furthermore, it has been demonstrated that certain histologic types express markers associated with distinct maturational stages of germ cell development, which presumably are dependent on a specific gonadal environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Testicular germ cell tumors show a characteristic association with a preinvasive carcinoma in situ, the testicular intratubular neoplasia. 7,31,42 No such in situ lesion has been seen in the brain of patients with CNS-GCT. Furthermore, it has been demonstrated that certain histologic types express markers associated with distinct maturational stages of germ cell development, which presumably are dependent on a specific gonadal environment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that certain histologic types express markers associated with distinct maturational stages of germ cell development, which presumably are dependent on a specific gonadal environment. 7,[43][44][45] Lastly, there are some data suggesting that the chromosomal marker characteristic of testicular germ cell tumors, the isochromosome 12p, plays only a minor role in CNS-GCTs. 18,22 As a consequence, it must be debated whether the information generated in the more frequent (and more easily assessable) testicular germ cell tumors can indeed be transferred to CNS-GCTs without scrutiny.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A somatic type of imprint, however, is erased by demethylation, while these cells migrate toward the genital ridges ϳ 10.5 dpc (Lee et al, 2002). The erasing of the methylation (imprint) of H19, Igf-2, Igf-2R, and Snrpn in early PGC could be envisioned as one of the mechanisms that shuts down PGC developmental pluripotency and makes these cells resistant to potential parthenogenesis or formation of teratomas (Macchiarini and Ostertag, 2004;Oosterhuis and Looijenga, 2005). A proper somatic imprint is subsequently again reestablished in sperm and oocytes, so that a fertilized egg expresses a developmentally proper somatic imprint of these crucial genes.…”
Section: Regulation Of Pluripotency In the Germ Line By Status Of Sommentioning
confidence: 99%
“…In particular, seminoma cells mimic early germ cells, probably PGCs or gonocytes (Skakkebaek et al, 1987). Recent immunohistochemical data demonstrated that seminoma and embryonal carcinoma cells are positive for OCT3/4, suggesting TGCTs derive from PGCs (Looijenga et al, 2003;Rajpert-De Meyts et al, 2004;Oosterhuis and Looijenga, 2005).…”
Section: Introductionmentioning
confidence: 99%